Phase stability and strain accumulation in CdO as a function of Cd/O supply during MOVPE synthesis. (August 2018) - Venkatachalapathy, V.; Galeckas, A.; Azarov, A.; Vines, L.; Kuznetsov, A. Yu.
Abstract: A prominent trend for the stabilization of zincblende or wurtzite phases in CdO is observed. Typically, CdO occurs in its "equilibrium" rocksalt phase when grown on r-plane oriented sapphire substrates employing Cd-rich growth conditions. Gradual decrease of Cd supply, i.e. moving towards O-rich condition, results in additional phases, firstly zincblende and secondly wurtzite. Importantly, the variation of Cd/O ratios at the reaction zone was tuned by changing both the precursor flow rates and the growth temperature affecting the precursor decomposition. Moreover, an interesting strain accumulation trend, correlating with the band gap variations was observed as a function of Cd/O supply ratios too. In particular, a gradual change towards O-rich conditions leads to a build-up of strain in the films and red-shifts the optical absorption edge. Highlights: Cadmium oxide thin films grown by metal organic vapor phase epitaxy tuning cadmium/oxygen molar ratios. Leaning towards oxygen rich growth condition, stabilizes zinc blende and wurtzite phases. Strain evolution at the film/substrate interface as a function of growth temperature.